Modelling and control of dual boost DC-DC converter - Afreen Fajila (Nanyang Technological University, 2020)
The Interleaved Double Dual Boost Converter (IDDBC) is gaining popularity, and it has a promising solution for renewable energy and energy storage system in DC microgrids. As compared to conventional boost converters, the Interleaved Boost Converters have a significant advantage in reducing current ripples and produce high voltage outputs which are suitable for high power applications. However, when IDDBC operates under tightly controlled power loads in DC microgrids, it acts as the Constant Power Load (CPL), which makes the extensive signal system unstable. In this paper, a comprehensive study has been made on modelling and control techniques of Interleaved Double Dual Boost (IDDB) converter. The MATLAB/ Simulink model has been constructed to study the efficiency of high voltage and reduced ripple current output. For better stability and high voltage output for DC microgrid system, Non-Linear Disturbance Observer (NDO) -based backstepping controller with Interleaved Double Dual Boost Converter is modelled and studied.